Synergistic Integrated Business Model-Sustainability-Technology of Top Malaysian Oil and Gas PLCs: The Moderating Role of United Nations SDG 5 - Baharudin, Dayana Mastura; Marimuthu, Maran (Business Management and Strategy, 2021)
Purpose – This study investigates the impact of the three main determinants of strengthening the sustainability practices of the oil and gas public listed companies of Bursa Malaysia (PLCs) through the Business Model, Sustainability and Technology synergistically compared between pre and post Malaysian Code of Corporate Governance 2017 (MCCG 2017). Design/methodology/approach – The study has followed the purposive sampling method followed by descriptive statistics, regression analysis and content analysis derived from the Malaysian Code of Corporate Governance 2012 (MCCG 2012) and the MCCG 2017 together with previous studies of the analysis of the annual reports and integrated reports in order to explore the reporting of the business model, sustainability and technology as a synergy.